2019
DOI: 10.1038/s41598-019-49162-5
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Body Composition using Dual energy X-ray Absorptiometry and Type-2 Diabetes: A Systematic Review and Meta-Analysis of Observational studies

Abstract: The association between objective measures of body composition (BC) with type 2 diabetes (T2DM) is inconclusive. We conducted a systematic review and meta-analysis to examine the association between several body composition (BC) indices assessed using dual energy X-ray absorptiometry (DXA), and T2DM. Using PRISMA guidelines, we searched for observational studies investigating BC measures, including total body fat mass (BFM), visceral fat mass (VFM), subcutaneous fat mass (SFM), and fat free mass (FFM); and T2D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
32
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 62 publications
(75 reference statements)
5
32
1
Order By: Relevance
“…In the present study, since the PAD patients with more proximal lesions of above the knee of iliac, femoral, and popliteal arteries were enrolled [15], the negative association between PAD and change in the thigh muscle area was elucidated. The findings of the present study were in line with those of a previous reports wherein diabetic patients were at risk of losing their skeletal muscle mass [2,22]. In another study, a large numbers of PAD patients suffered from peripheral neuropathy complicated with diabetes, which led to immobility losing their skeletal muscle [20].…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, since the PAD patients with more proximal lesions of above the knee of iliac, femoral, and popliteal arteries were enrolled [15], the negative association between PAD and change in the thigh muscle area was elucidated. The findings of the present study were in line with those of a previous reports wherein diabetic patients were at risk of losing their skeletal muscle mass [2,22]. In another study, a large numbers of PAD patients suffered from peripheral neuropathy complicated with diabetes, which led to immobility losing their skeletal muscle [20].…”
Section: Discussionsupporting
confidence: 92%
“…A prospective study found that total reduction in LBM was not significantly associated with incidence of diabetes . Moreover, even if a meta‐analysis found lower LBM levels in individuals with diabetes, this study failed to conclude that LBM was significantly associated with a reduction in the odds of MetS and suggest that this association is uncertain …”
Section: Introductionmentioning
confidence: 78%
“…5 Lean body mass is the primary site of glucose uptake 8 ; and therefore, it has been suggested that LBM protects against cardio-metabolic risk factors and diabetes. 9,10 Although rational, few studies support that both BMI and high-LBM are independently associated with unfavorable cardio-metabolic profiles. 5,11 For example, a study including 421 men and women suggests that age and LBM (but not fat mass) explained 46% of the unfavorable cardio-metabolic risk factors profile.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, most individuals with T2D are overweight or obese, 11 and T2D patients who are not considered overweight or obese may still have a high percentage of body fat primarily in the abdominal region. [11][12][13] Current studies have indicated that impaired glycemic control and disease duration are the two major contributing factors that affect body composition in individuals with T2D. 14,15 However, data about fat distribution and variations in individuals with T2D are limited and equivocal.…”
Section: Introductionmentioning
confidence: 99%